New records and an illustrated taxonomic key to the genera of the tribe Stenodemini (Hemiptera: Miridae) in Iran - Mozhgan Zamani; Reza Hosseini; Fedor V. Konstantinov (Journal of Insect Biodiversity and Systematics)
During the spring-summer of 2020–2022, field investigations were conducted in the diverse climate regions along the southern shore of the Caspian Sea. Examination of the sampled material resulted in the finding of Acetropis carinata (Herrich-Schaeffer, 1841) as a new genus and species for the Iranian fauna. Additionally, four more species were found: Leptopterna inopinata Vinokurov, 1982 and Stenodema (Brachystira) pilosa (Jakovlev, 1889) in Ardabil province, Stenodema (Stenodema) virens (Linnaeus, 1767) in Ardabil and Guilan provinces, and Megaloceroea recticornis (Geoffroy, 1785) in Mazandaran province. Measurements, distributional information, dorsal and lateral habitus photographs, illustrations of male and female genitalia, as well as diagnoses and redescriptions are provided for the new country and province records. A revised key was compiled for the identification of all Stenodemini genera currently known from Iran.